Understanding how Grade 11 life sciences teachers mediate biodiversity concepts in a second language context : a case study - Gqoloqa, Zingisa (Rhodes University, Faculty of Education, Department of Education, 2015)
This research focused on an investigation of the pedagogy and strategies used by Grade 11 Life Sciences teachers when mediating Biodiversity concepts with English second language learners. My interest in this investigation was triggered by the Examiners' Reports for Life Sciences from 2009 to 2012 which consistently noted learner challenges in answering, interpreting and analysing questions during exams. The reports highlighted learners' lack of understanding of the questions which led to them providing irrelevant information in their exam scripts. These reports claimed that challenges experienced by these learners could be attributed to language issues experienced by English second language learners. Influenced by these reports, a qualitative case study of two Senior Secondary schools in East London, Eastern Cape South Africa was conducted. Underpinned by an interpretive paradigm and driven by the desire to achieve an in-depth understanding of the case under study, three phases of information gathering were followed. The first phase was that of gathering information through document analysis. Documents were analysed to gain insights and understanding of the issue before conducting interviews. The next phase was that of gathering information through semi-structured interviews followed by classroom observations. Findings from these observations were verified through stimulated recall interviews which provided clarity on the intentionality of choosing a certain method and strategy over another when assisting learners in making meaning of biodiversity concepts. The main findings of this study are that factors which limit learner understanding of biodiversity concepts are a result of a combination of factors such as failure to interpret questions, spelling problems which alter meaning of concepts and an inability to make distinctions among closely related concepts within the topic of Biodiversity. Responding to these factors, teachers demonstrated knowledge of a variety of teaching strategies to support learners. The choice of teaching strategies seemed to be guided by their experiences as well as the challenges they often encounter. Furthermore, teachers' reflections on their practice provided opportunities for them to identify strengths and limitations of their choice of strategies and possibilities for improvement. It was also noted that factors such as large class sizes, gaps in content knowledge and a lack of detail in chalkboard summary limited the effectiveness of their teaching strategies. The study recommends that: "¢ Teacher-learner ratio needs to be considered for effective support; "¢ There is still a need to capacitate educators in environmental education. In-service training should focus on developing teacher understanding of foundational knowledge in life sciences; and "¢ Teachers need to improve their chalkboard summary skills to increase the level of support that could be provided by comprehensive chalkboard summary through the elaboration of ideas
Keywords: Life sciences -- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Language and education